\(=\left(3-8+\dfrac{1}{2}-\dfrac{1}{2}\right)-\left(\dfrac{4}{5}+\dfrac{1}{5}\right)-1\)
\(=-5-1-1=-7\)
\(=\left(3-8+\dfrac{1}{2}-\dfrac{1}{2}\right)-\left(\dfrac{4}{5}+\dfrac{1}{5}\right)-1\)
\(=-5-1-1=-7\)
3\(\dfrac{1}{2}\) - \(\dfrac{4}{5}\) - 8\(\dfrac{1}{2}\) - \(\dfrac{1}{5}\) - (2021)^0
tính
Câu 1: Thực hiện phép tính
a, \(40\dfrac{1}{4}:\dfrac{5}{7}-25\dfrac{1}{4}:\dfrac{5}{7}-\dfrac{1}{2021}\)
b, \(\left|\dfrac{-5}{9}\right|.\sqrt{81}-2021^0.\dfrac{16}{25}\)
Câu 2: Tìm x
\(3\left(x-\dfrac{1}{3}\right)-7\left(x+\dfrac{3}{7}\right)=-2x+\dfrac{1}{3}\)
1. So sánh
a) \(A=\dfrac{1}{2}+\dfrac{1}{2^2}+\dfrac{1}{2^3}+...+\dfrac{1}{2^{2020}}+\dfrac{1}{2^{2021}}\) và B= \(\dfrac{1}{3}+\dfrac{1}{4}+\dfrac{1}{5}+\dfrac{13}{60}\)
b) \(C=\dfrac{2019}{2021}+\dfrac{2021}{2022}\) và \(D=\dfrac{2020+2022}{2019+2021}.\dfrac{3}{2}\)
Thực hiện phép tính:
a) 2021 - \(\left(\dfrac{1}{3}\right)^2\) . 32
b \(\dfrac{5}{10}\) + 9 . \(\dfrac{-3}{2}\)
c) -10 . \(\left(-\dfrac{2021}{2022}\right)^0\) + \(\left(\dfrac{2}{5}\right)^2\) : 2
Tổng \(S=\left(-\dfrac{1}{5}\right)^0+\left(-\dfrac{1}{5}\right)^1+\left(-\dfrac{1}{5}\right)^2+...+\left(-\dfrac{1}{5}\right)^{2021}\)có giá trị là
Bài 1:
a,\(3^7\) : \(3^5\)- \(\left(\dfrac{5}{17}\right)^0\) b,\(\left(\dfrac{5}{2}\right)^{13}\) : \(\left(\dfrac{1}{2}+2\right)^3\) c, 8.\(\left(\dfrac{1}{4}\right)^3\) +\(\left(\dfrac{2}{27}\right)^0\) - \(\dfrac{1}{8}\)
Bài 2 :
a, \(\dfrac{3^4.4^4}{6^4}\) b,\(\dfrac{15^3}{10^3}\) c, \(\dfrac{4^2.12^5}{9^2.2^{10}}\) d, \(\dfrac{6^2+5.2^2+4}{15}\)
Bài 3 :
a, \(\dfrac{\left(\dfrac{2}{3}\right)^3.\left(\dfrac{-3}{4}\right)^2.\left(-1\right)^5}{\left(\dfrac{2}{5}\right)^2.\left(\dfrac{-5}{12}\right)^2}\) b,\(\dfrac{6^6+6^3.3^3+3^6}{-73}\)
Mọi người giúp mình nhé mình sẽ cho bạn 1 like
2. Tìm x
a. \(\dfrac{4}{5}-3.\left|x\right|=\dfrac{1}{5}\) b. \(4x-\dfrac{1}{2}x+\dfrac{3}{5}x=\dfrac{4}{5}\)
c. (2x-8)(10-5x)=0 d. \(\dfrac{3}{4}+\dfrac{1}{4}\left|2x-1\right|=\dfrac{7}{2}\)
Bài 1:
a)So sánh \(\left(\dfrac{3}{4}\right)^{2021}+1với\dfrac{3}{4}+1\)
b)Cho x,y,z khác 0 thỏa mãn
\(\dfrac{2x-3}{5}=\dfrac{5y-2z}{3}=\dfrac{3z-5x}{2}\)
Tính GTBT: B=\(\dfrac{12x-5y-3z}{x-3y+2z}\)
a) \(2\dfrac{1}{2}\) - x + \(\dfrac{4}{5}\) = \(\dfrac{2}{3}\) - (\(-\dfrac{4}{7}\) )
b) \(-\dfrac{4}{7}\) - x = \(\dfrac{3}{5}\) - 2x
c) (\(\dfrac{3}{8}\) - \(\dfrac{1}{5}\) ) + (\(\dfrac{5}{8}\) - x) = \(\dfrac{1}{5}\)